The Effects of Firms Characteristics on the Growth of Medium and Small Business in Developing Country (Case Study Ethiopia) (Global Journal of Management and Business Research, 2016)
The effects of firms' characteristics on the growth of medium and small business in developing country. This study is important to both academic research and policy development because of the significant contribution these businesses could make to economic development, the growth of employment and the generation of new innovations. For research design; crosssectional, descriptive and inferential designs study were used in the study. The study used both primary and secondary data. Pertaining to data analysis the researchers used quantitative data analysis techniques mainly descriptive analysis using percentages, tables and mean were employed. While for inferential statistics like, chi-square and ANOVA were used to test the statistically significant difference (independency) of variables, and statistically significant mean difference among different business sectors. Hence, as per result of this study majority of small and medium enterprise were far from raw materials. The farness of the firms from raw material may negatively affect their growth of small and medium business Majority of the small and medium businesses in Ethiopia are either owned by a single individual or are family businesses.
Keywords: inferential statistics like; chi-square and ANOVA